The Virtual Ballet Studio: A Phenomenological Enquiry into the Domestic as Dance-Space During Lockdown - Ferrer-Best, Francesca (The International Journal of Screendance, 2021)
The paper is based on an autoethnographic study of dancing via Zoom over the Covid19 lockdown in Sydney, Australia. Its theoretical framework takes up Iris Marion Young's critical phenomenology and work on domestic space to think about certain focal points of the experience, such as having a room to move in, the floor, and the screen. The aim is to examine how important dance-space is to the experience of dancing, and what the specifics of our current situation have revealed about dancing that were obscured to a greater extent before: for instance, the embeddedness of a dancer in their context and what this means for thinking about privilege, as well as the curatorial work that goes into making domestic space an aestheticized dance-space. In this way, I propose that Zoom classes, as well as being a distinct new phenomenon, also have much to teach us about 'conventional,' pre-Covid dance practice.